The factors affecting biochar application in restoring heavy metal-polluted soil and its potential applications. Issue 2 (7th February 2018) - Xu, Min; Wu, Jun; Luo, Ling; Yang, Gang; Zhang, Xiaohong; Peng, Hong; Yu, Xiaoyu; Wang, Lilin
ABSTRACT: Heavy metal soil contamination is being given more and more attention due to increasing threats of heavy metals to soil quality, ecological function and human health. Biochar application is an effective way to remove toxic metals due to its high efficiency and low price. Electrostatic adsorption is the primary adsorption mechanism. The absorption ability and stability of biochar is the key to its adsorption performance. The extent of the restoration efficiency is dependent on many factors. The biomass, pyrolysis temperature and application rate affect the number of binding sites. The ageing process and soil properties significantly affect the biochar stability. For long-term purposes, biochar derived from woody residues and pyrolysed at high temperatures is the best available material. In addition, the application of alkaline and electronegative biochar to clay-rich, acidic and As- or Cr-contaminated soil should to be treated with caution.